2020
DOI: 10.3390/cells9020376
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Influence of the Intestinal Microbiome Through Dietary Intervention and Bowel Cleansing Might Improve Motor Symptoms in Parkinson’s Disease

Abstract: The impact of the gut microbiome is being increasingly appreciated in health and in various chronic diseases, among them neurodegenerative disorders such as Parkinson’s disease (PD). In the pathogenesis of PD, the role of the gut has been previously established. In conjunction with a better understanding of the intestinal microbiome, a link to the misfolding and spread of alpha-synuclein via inflammatory processes within the gut is discussed. In a case-control study, we assessed the gut microbiome of 54 PD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 80 publications
1
66
0
Order By: Relevance
“…More recently, a German population-based cohort study tested whether a dietary intervention (i.e., ovo-lacto vegetarian diet including SCFA for 14 days) alone or combined with an additional physical colon cleaning (i.e., daily fecal enema over 8 days) may lead to changes of the gut microbiota in PD patients. Their results showed significant improvement in the Unified PD rating scale III (UPDRS III) score after the dietary intervention combined with fecal enema after a one-year follow-up [ 297 ]. Interestingly, another study showed neuroprotective effects of Vitis vinifera red grape seed and skin extract (GSSE) on midbrain dopaminergic neurons, both in vitro and in vivo, against 6-OHDA-induced toxicity [ 298 ].…”
Section: Targeting the Gut–brain Axis In Pdmentioning
confidence: 99%
“…More recently, a German population-based cohort study tested whether a dietary intervention (i.e., ovo-lacto vegetarian diet including SCFA for 14 days) alone or combined with an additional physical colon cleaning (i.e., daily fecal enema over 8 days) may lead to changes of the gut microbiota in PD patients. Their results showed significant improvement in the Unified PD rating scale III (UPDRS III) score after the dietary intervention combined with fecal enema after a one-year follow-up [ 297 ]. Interestingly, another study showed neuroprotective effects of Vitis vinifera red grape seed and skin extract (GSSE) on midbrain dopaminergic neurons, both in vitro and in vivo, against 6-OHDA-induced toxicity [ 298 ].…”
Section: Targeting the Gut–brain Axis In Pdmentioning
confidence: 99%
“…Dietary interventions and bowel cleansing are sufficient methods to impact the gut microbiome in patients with PD. Therefore, a positive impact on the clinical course is feasible [19] . Professor Braak in his hypothesis on 6 stage pathogenesis of PD has mentioned caudorostral trajectory of pathology in brain.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…This diet, along with rectal enemas for a short period of time, may result in a lower levodopa requirement. 101 In the study by Hegelmaier et al, enemas were used to manage constipation and were also noted to decrease levels of Clostridiaceae and an increase in microbial diversity. 101 Direct supplementation of short chain fatty acids may be neuroprotective and have anti-inflammatory properties for PD.…”
Section: Treatment Optionsmentioning
confidence: 99%